Telaah Kurikulum K13 Pendidikan Agama Islam di Madrasah Tsanawiyah Darul Muttaqien - Dian Eka Wati; Nur Ayu Suci Lestari; Dwi Noviani (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The implementation of the 2013 curriculum began in the 2013 school year with a coba tahap that benefited the more disadvantaged schools. Initially, this curriculum is taught in lower grades, such as grades I and IV for Dasar School, grades VII for Primary School, and grades X for Upper School/Kejuruan School. Over time, this curriculum is needed to cover more ground in various educational settings.One of the primary guidelines in the 2013 curriculum is the application of knowledge to four areas of study: comprehension, application, sikap, and research. The purpose of the curriculum is to evaluate students not only on the basis of their academic performance but also on their moral and social development. This aspek-aspek integration aims to provide a holistic approach to teaching.